(untitled) - Viner, Daniel; Stierle, Matthias; Matzner, Martin (Proceedings of the ICPM Doctoral Consortium and Tool Demonstration Track 2020 co-located with the 2nd International Conference on Process Mining (ICPM)
www.processmining-software.com is a dedicated website for process mining software comparison and was developed to give practitioners and researchers an overview of commercial software available on the market. Based on literature review and experimental software testing, a set of criteria was developed in order to assess the tools’ functional capabilities in an objective manner. With our publicly accessible website, we intend to increase the transparency of software functionality. Being an academic endeavour, the non-commercial nature of the study ensures a less biased assessment as compared with reports from analyst firms.<br